Diagnosis and gestational follow-up in a patient with Herlyn-Werner-Wünderlich syndrome, a case report - Laura Baños Cándenas; Daniel Abehsera Davó; Marta de la Peña Rodríguez de Medina; Jessica Martín Orlando; Andrés Carlos López Díaz (Taiwanese Journal of Obstetrics & Gynecology, 2019)
Objective: Herlyn-Werner-Wünderlich syndrome (HWW) is a rare congenital malformation of the urogenital tract due to a fusion failure in the Müllerian ducts. This anomaly consists of a didelphus uterus with obstructed hemivagina and sometimes associated with ipsilateral renal agenesis. The treatment of choice is surgical, it consists of a simple procedure of resection of the vaginal septum and drainage of the obstructed hemivagina and retained collections. Case report: We report the case of a pregnancy in a 37-year-old woman with SHWW without resection of the vaginal septum. Conclusions: The early detection is important due to the possible associated complications. Women with uterine defects are subject to an increased risk of complications in pregnancy and childbirth. Therefore, each case must be treated individually.